2020
DOI: 10.3389/fbioe.2020.588210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co-culture on Improved Productivity and Bioresource for Microalgal Biomass Using the Floc-Forming Bacteria Melaminivora Jejuensis

Abstract: Bacterial and algal floc formation was induced by inoculating three species of wastewater-derived bacteria (Melaminivora jejuensis, Comamonas flocculans, and Escherichia coli) into algal cultures (Chlorella sorokiniana). Bacterial and algal flocs formed in algal cultures inoculated with M. jejuensis and C. flocculans, and these flocs showed higher sedimentation rates than pure algal culture. The floc formed by M. jejuensis (4988.46 ± 2589.81 μm) was 10-fold larger than the floc formed by C. flocculans (488.60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Previous studies have determined the optimal growth temperature conditions for Chlorella vulgaris and Chlorella sorokiniana (Yun et al, 2020). Furthermore, it was found that an organic carbon source in a heterotrophic condition could be utilized by Chlorella (Kim et al, 2020). In this study, we evaluated the applicability and usability of glucose as an organic carbon source for Chlorella vulgaris (KNUA104) and Chlorella sorokiniana (KNUA114 and KNUA122) strains under heterotrophic and mixotrophic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have determined the optimal growth temperature conditions for Chlorella vulgaris and Chlorella sorokiniana (Yun et al, 2020). Furthermore, it was found that an organic carbon source in a heterotrophic condition could be utilized by Chlorella (Kim et al, 2020). In this study, we evaluated the applicability and usability of glucose as an organic carbon source for Chlorella vulgaris (KNUA104) and Chlorella sorokiniana (KNUA114 and KNUA122) strains under heterotrophic and mixotrophic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the bacterial strains tested, M. jejuensis formed the largest floc with C. sorokiniana , with the highest sedimentation ability. Furthermore, the M. jejuensis co-culture improved biomass and lipid productivity compared with the pure algal culture [ 101 ].…”
Section: Co-cultivation With Bacteria Yeast or Other Microalgaementioning
confidence: 99%
“…Although Melaminivora species have not yet been studied thoroughly, they are known to have several antibacterial resistance genes [6]. In addition, Melaminivora jejuensis is used in activated sludge systems as part of industrial water treatment bioreactors since it is a floc-forming bacterium [7]. Here, we report a bacterial strain SC2-9 T as representing a new species that was isolated during the study of the population structure of the pigpen in Republic of Korea.…”
Section: Introductionmentioning
confidence: 99%